McGraw-Hill's hazardous chemical safety guide for the plastics industry - Pohanish, Richard P. (McGraw-Hill, 2000)
An intensive, ready-to-use outline of the all the necessary occupational and environmental health and safety information on the 400 most important chemicals in the plastics industry